Enlightened leadership and its impact on workplace harmony: An analytical study of the opinions of a sample of healthcare staff working in some private hospitals - Amer Hamoud Al-Karawi , Fatima; Hurajah Al-Hasnawi, Hussein (Iraqi Journal for Administrative Sciences, 2026)
The study aimed to determine the level of impact of enlightened leadership on enhancing workplace harmony through an analytical survey of the opinions of a sample of healthcare staff working in some private hospitals. Enlightened leadership was measured through six dimensions: role model, developer, servant, visionary, communicator, and change agent. Workplace harmony was measured through several dimensions related to the relationships and interactions among employees within the organization. The study population consisted of healthcare staff working in the hospitals under study, and a random sample of (173) doctors and nurses was selected. A questionnaire was used as the main tool for data collection. The data were analyzed using several statistical methods, including the normal distribution test, confirmatory factor analysis, descriptive statistics, Pearson correlation analysis, and structural equation modeling to test the research hypotheses. The results revealed significant correlation and effect relationships between enlightened leadership and workplace harmony, indicating its role in promoting a more harmonious and cooperative work environment.